2018
DOI: 10.2106/jbjs.17.00251
|View full text |Cite
|
Sign up to set email alerts
|

Capsular Ligament Function After Total Hip Arthroplasty

Abstract: Background: The hip joint capsule passively restrains extreme range of motion, protecting the native hip against impingement, dislocation, and edge-loading. We hypothesized that following total hip arthroplasty (THA), the reduced femoral head size impairs this protective biomechanical function. Methods: In cadavers, THA was performed through the acetabular medial wall, preserving the entire capsule, and avoiding the targeting of a particular surgical approach. Eight hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Previous anatomical studies have described the ILFL in detail [9,11,[13][14][15][16]. The present study also investigated the anatomical features of the ILFL, including its origin and size.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Previous anatomical studies have described the ILFL in detail [9,11,[13][14][15][16]. The present study also investigated the anatomical features of the ILFL, including its origin and size.…”
Section: Discussionmentioning
confidence: 91%
“…The hip capsule includes three main ligaments, namely, the iliofemoral ligament (ILFL), ischiofemoral ligament (ISFL), and pubofemoral ligament, which form a lining surrounding the hip joint and are thought to stabilize the joint [1][2][3][4][5][6]. Preservation or reconstruction of these capsular ligaments is important in modern hip joint surgeries, such as arthroplasty, arthroscopy, and open surgical procedures [7][8][9][10][11]. In particular, minimally invasive surgery has become a focus in total hip arthroplasty (THA), and preservation of the hip capsule is an important consideration [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an effort to characterize capsular function after total hip arthroplasty, van Arkel et al inserted the femoral head, neck, and cup implants through a cotyloid fossa portal and, by doing so, preserved the entire intact joint capsule 77 . The authors reported that the smaller head sizes removed the natural tensioning ability of the capsule to restrain rotational motion (Fig.…”
Section: Surgical Managementmentioning
confidence: 99%